Heat insulation fabric and preparation method thereof
Through wet spinning of modified silica aerogel and polyamide fiber and high-temperature oxidation acrylic acid technology, thermal insulation fabrics are produced, which solves the problems of heat insulation and ultraviolet damage in high-temperature environments, and achieves efficient thermal insulation and UV-proof effect improves the tensile strength and thermal conductivity of the fabric.
Patent Information
- Application Number
- CN202411190994.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing clothing materials cannot be effectively insulated under high temperature environments, resulting in heat stress and are damaged by ultraviolet rays, affecting human health and clothing life.
Modified silica aerogel and polyamide fiber wet spinning, and then oxidize acrylic acid at high temperature to make thermal insulation fabrics. The nanotitanium dioxide absorbs, reflects and scatters ultraviolet rays, improves thermal insulation performance, and enhances nanostructure by adjusting magnetic field. Tensile strength and thermal conductivity.
It achieves efficient heat insulation and UV protection, improves the tensile strength and thermal conductivity of the fabric, ensures wearer safety and extends the life of the clothing.
Smart Images

Figure BDA0005015090620000061 
Figure BDA0005015090620000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a heat-insulating fabric and a preparation method thereof. Background Art
[0002] As people's requirements for clothing become higher and higher, while pursuing fashion trends and functionality, they also pay more attention to the comfort of clothing. But fundamentally, comfort is always the main demand of the general public for clothing. The thermal comfort of clothing not only affects the comfort of wearing clothing, but also affects the heat stress of the wearer, thereby affecting various stress physiological reactions of the human body, and even endangering life safety. For example, when firefighters are working in high-temperature fire scenes, heat will accumulate in their armpits and backs. If the fire suits cannot evacuate this accumulated heat in time, heat stress is likely to occur, threatening the personal safety of firefighters.
[0003] In addition, studies have shown that the human skin is highly sensitive to temperature, especially under external temperatures. When the body temperature reaches 45°C, people will feel obviously uncomfortable and experience dizziness, fatigue, heat stroke, etc. In severe cases, the skin will feel burning. When the body temperature rises to 72°C, it will not only cause second-degree burns to the skin, but also endanger life safety.
[0004] At the same time, with the development of science and technology, the level of industrialization has gradually improved. Its production technology has also been improved, and a large amount of fluorine and chlorine compounds have been discharged into the atmosphere, causing the ozone layer to be increasingly damaged. The amount of ultraviolet radiation reaching the ground has increased. Excessive ultraviolet rays can reduce the immune function of the human body, which is very harmful to the human body. It can not only increase the melanin in the human body and age the skin, but also cause diseases such as skin cancer. In addition, ultraviolet rays also have an adverse effect on clothing, which can make clothing fade, and can also make fibers such as nylon and cellulose embrittled and strongly reduced. Therefore, the present invention studies and prepares a fabric with good heat insulation effect and anti-ultraviolet. Summary of the invention
[0005] The object of the present invention is to provide a thermal insulation fabric and a preparation method thereof to solve the problems existing in the prior art.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a thermal insulation fabric, which is prepared by wet spinning of modified silica aerogel and polyamide fiber and then high-temperature oxidation of acrylic acid.
[0007] Furthermore, the modified silica aerogel is prepared by adding acrylic acid, polyurethane and tetrabutyl titanate into the silica aerogel, and then using the modified polyurethane to catalyze tetrabutyl titanate to prepare nano titanium dioxide.
[0008] (1) mixing a dispersant, a wetting dispersant and deionized water in a mass ratio of 0.11-0.15:0.09-0.11:1, ultrasonicating at 30-40 kHz for 10-30 minutes, stirring at 700-800 r / min for 1-2 hours to obtain a mixed solution, adding 0.07-0.08 times the mass of the mixed solution of silica aerogel, stirring at 800-1000 r / min for 30-60 minutes to obtain a reaction solution;
[0009] (2) adding 2 / 3 of the titanium dioxide reaction solution to the reaction solution, and dropping the remaining 1 / 3 of the titanium dioxide reaction solution under stirring at 500-600 r / min. After the dropping is completed, standing at room temperature for 4-5 hours, adding 0.2-0.3 times the mass of the reaction solution of pretreated polyamide pellets, stirring at 200-300 r / min for 3-6 hours, and standing at room temperature for 4-5 hours to obtain a spinning solution;
[0010] (3) performing wet spinning and weaving under a stable magnetic field to obtain a fabric;
[0011] (4) The fabric is evaporated for 3 hours at 180-200°C, 0.5-0.6 MPa and nitrogen protection, and then washed to obtain the thermal insulation fabric.
[0012] Furthermore, in step (1), the dispersant is one of SN-5040, DN500 and HY-1010; and the wetting dispersant is one of PE-100, LD-1055 and HR-8060.
[0013] Furthermore, the preparation method of the titanium dioxide reaction liquid in step (2) is: PU500 polyurethane, tetrabutyl titanate, and acrylic acid are mixed in a mass ratio of 1 to 2:0.5 to 1:1, the mass ratio of polyurethane to silica aerogel is 1, and then 2 to 3 times the total mass of 50wt% ethanol aqueous solution is added, and stirred at 600 to 800 r / min for 4 to 6 hours.
[0014] Furthermore, the preparation method of the pretreated polyamide pellets in step (2) is: mixing the polyamide pellets with the TEGIN Pellets aqueous solution at a ratio of 1:10, soaking for 4 to 6 hours, and then drying them in a vacuum drying oven at 100 to 120° C. and 50 to 60 kPa for 2 to 3 hours.
[0015] Furthermore, the concentration of TEGIN Pellets in the TEGIN Pellets aqueous solution is 30-40 g / L.
[0016] Furthermore, the process parameters of the wet spinning in step (4) are: the spinning temperature is 60-70° C., the aqueous solution of dimethyl sulfoxide is used as the coagulation bath, and the coagulation bath concentration is 50wt%-60wt%.
[0017] Furthermore, the magnetic field strength of the stable magnetic field in step (4) is 0.35-0.5T.
[0018] Furthermore, in the step (4), the washing is performed by heating the fabric precursor with deionized water at a constant temperature of 60 to 70° C. in a water bath for 10 to 15 minutes, drying at 70° C., then heating with anhydrous ethanol at a constant temperature of 40 to 50° C. in a water bath for 10 to 15 minutes, ultrasonically treating with 20 to 25 kHz for 10 to 15 minutes, drying at 70° C., and then repeating the deionized water washing for 2 to 3 times.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention uses a magnetic field to assist in wet spinning of modified silica aerogel and polyamide fiber, and then oxidizes acrylic acid at high temperature to prepare a heat-insulating fabric, so as to achieve the effects of heat insulation and UV protection.
[0021] First, polyurethane, tetrabutyl titanate and acrylic acid are added to the silica aerogel. Acrylic acid is used to enhance the amino activity on the surface of polyurethane. Then polyurethane catalyzes tetrabutyl titanate to prepare nano-titanium dioxide. At the same time, polyurethane can improve the mechanical properties of silica aerogel, and it can also be used as a viscous agent to make the silica particles combine more firmly. Nano-titanium dioxide can absorb, reflect and scatter ultraviolet rays, has excellent anti-ultraviolet effect, and can further improve the thermal insulation performance of the fabric.
[0022] Secondly, a magnetic field is applied to assist the wet spinning of modified silica aerogel and polyamide fiber, and then acrylic acid is decomposed at high temperature to produce thermal insulation fabric; the application of a magnetic field will adjust the morphology of nano-titanium dioxide and improve its UV protection effect; after the decomposition of acrylic acid, slender nano-grooves and holes will be left in the fabric. The introduction of slender nano-groove structure can greatly increase the contact area between fibers, thereby improving the interface interaction. This interface effect makes a great contribution to friction, which increases the tensile strength of the material by several times. Nano-grooves and holes can greatly increase the heat transfer path, so that the fabric has an ultra-low thermal conductivity, achieving the effect of heat insulation and UV protection. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the test methods of various indicators of the thermal insulation fabrics prepared in the following examples are as follows:
[0025] Thermal conductivity: The thermal insulation properties of the thermal insulation fabrics prepared in the embodiment and the comparative example of the same area were tested with reference to GB / T 11048-2018 “Determination of thermal resistance and moisture resistance of textiles under steady-state conditions for physiological comfort (evaporative hot plate method)”.
[0026] Anti-ultraviolet performance: The thermal insulation fabrics of the same area prepared in the embodiment and the comparative example were tested for their anti-ultraviolet performance with reference to GB / T 18830-2009 “Evaluation of Anti-ultraviolet Performance of Textiles”.
[0027] Tear resistance: The thermal insulation fabrics of the embodiment and the comparative example with the same area were subjected to a tear strength test according to GB / T529.
[0028] Example 1
[0029] A method for preparing a thermal insulation fabric comprises the following steps:
[0030] (1) Dispersant SN-5040, wetting dispersant PE-100 and deionized water were mixed in a mass ratio of 0.11:0.09:1, ultrasonicated at 30 kHz for 10 minutes, stirred at 700 r / min for 1 hour to obtain a mixed solution, added with silica aerogel in an amount of 0.07 times the mass of the mixed solution, and stirred at 800 r / min for 30 minutes to obtain a reaction solution;
[0031] (2) PU500 polyurethane, tetrabutyl titanate, and acrylic acid were mixed in a mass ratio of 1:0.5:1, with the mass ratio of polyurethane to silica aerogel being 1, and then a 50wt% ethanol aqueous solution twice the total mass was added, and the mixture was stirred at 600 r / min for 4 h to obtain a titanium dioxide reaction solution;
[0032] (3) The polyamide pellets were mixed with a 30 g / L TEGIN Pellets aqueous solution at a ratio of 1:10, soaked for 4 h, and then dried in a vacuum drying oven at 100° C. and 50 kPa for 2 h to obtain pretreated polyamide pellets;
[0033] (4) adding 2 / 3 of the titanium dioxide reaction solution to the reaction solution obtained in step (1), and dropping the remaining 1 / 3 of the titanium dioxide reaction solution under stirring at 500 r / min. After the dropping is completed, standing at room temperature for 4 hours, adding 0.2 times the mass of the reaction solution of pretreated polyamide pellets, stirring at 200 r / min for 3 hours, and standing at room temperature for 4 hours to obtain a spinning solution;
[0034] (5) performing wet spinning in a stable magnetic field with a magnetic field strength of 0.35 T, a spinning temperature of 60° C., an aqueous solution of dimethyl sulfoxide as a coagulation bath, a coagulation bath concentration of 50 wt %, and weaving to obtain a fabric;
[0035] (6) The fabric was evaporated at 180°C, 0.5 MPa and nitrogen protection for 3 h to obtain a fabric precursor, and the fabric precursor was heated in a constant temperature water bath at 60°C with deionized water for 10 min, dried at 70°C, and then heated in a constant temperature water bath at 40°C with anhydrous ethanol for 10 min, ultrasonically treated at 20 kHz for 10 min, and dried at 70°C. The deionized water washing was repeated twice, and the thermal insulation fabric was dried at 70°C.
[0036] Example 2
[0037] A method for preparing a thermal insulation fabric comprises the following steps:
[0038] (1) Dispersant SN-5040, wetting dispersant PE-100 and deionized water were mixed in a mass ratio of 0.13:0.10:1, ultrasonicated at 35 kHz for 20 minutes, stirred at 750 r / min for 1.5 hours to obtain a mixed solution, added with silica aerogel in an amount of 0.075 times the mass of the mixed solution, and stirred at 900 r / min for 45 minutes to obtain a reaction solution;
[0039] (2) PU500 polyurethane, tetrabutyl titanate, and acrylic acid were mixed in a mass ratio of 1.5:0.8:1, and the mass ratio of polyurethane to silica aerogel was 1, and then 2.5 times the total mass of 50wt% ethanol aqueous solution was added, and stirred at 700r / min for 5h to obtain a titanium dioxide reaction solution;
[0040] (3) The polyamide pellets were mixed with a 35 g / L TEGIN Pellets aqueous solution at a ratio of 1:10, soaked for 5 h, and then dried in a vacuum drying oven at 110° C. and 55 kPa for 2.5 h to obtain pretreated polyamide pellets;
[0041] (4) adding 2 / 3 of the titanium dioxide reaction solution to the reaction solution obtained in step (1), and dropping the remaining 1 / 3 of the titanium dioxide reaction solution under stirring at 550 r / min. After the dropping is completed, standing at room temperature for 4.5 hours, adding 0.25 times the mass of the reaction solution of pretreated polyamide pellets, stirring at 250 r / min for 4.5 hours, and standing at room temperature for 4.5 hours to obtain a spinning solution;
[0042] (5) performing wet spinning in a stable magnetic field with a magnetic field strength of 0.45 T, a spinning temperature of 65° C., an aqueous solution of dimethyl sulfoxide as a coagulation bath, a coagulation bath concentration of 55 wt %, and weaving to obtain a fabric;
[0043] (6) The fabric was evaporated at 190°C, 0.55 MPa and nitrogen protection for 3 h to obtain a fabric precursor, and the fabric precursor was heated in a constant temperature water bath at 65°C with deionized water for 13 min, dried at 70°C, and then heated in a constant temperature water bath at 45°C with anhydrous ethanol for 13 min, ultrasonically treated at 22 kHz for 13 min, and dried at 70°C. The deionized water washing was repeated twice, and the thermal insulation fabric was obtained after drying at 70°C.
[0044] Example 3
[0045] A method for preparing a thermal insulation fabric comprises the following steps:
[0046] (1) Dispersant SN-5040, wetting dispersant PE-100 and deionized water were mixed in a mass ratio of 0.15:0.11:1, ultrasonicated at 40 kHz for 30 minutes, stirred at 800 r / min for 2 hours to obtain a mixed solution, added with silica aerogel in an amount of 0.08 times the mass of the mixed solution, and stirred at 1000 r / min for 60 minutes to obtain a reaction solution;
[0047] (2) PU500 polyurethane, tetrabutyl titanate, and acrylic acid were mixed in a mass ratio of 2:1:1, and the mass ratio of polyurethane to silica aerogel was 1, and then 3 times the total mass of 50wt% ethanol aqueous solution was added, and stirred at 800r / min for 6h to obtain a titanium dioxide reaction solution;
[0048] (3) mixing the polyamide pellets with a 40 g / L TEGIN Pellets aqueous solution at a ratio of 1:10, soaking for 6 hours, and drying in a vacuum drying oven at 120° C. and 60 kPa for 3 hours to obtain pretreated polyamide pellets;
[0049] (4) adding 2 / 3 of the titanium dioxide reaction solution to the reaction solution obtained in step (1), and dropping the remaining 1 / 3 of the titanium dioxide reaction solution under stirring at 600 r / min. After the dropping is completed, standing at room temperature for 5 h, adding 0.3 times the mass of the reaction solution of pretreated polyamide pellets, stirring at 300 r / min for 6 h, and standing at room temperature for 5 h to obtain a spinning solution;
[0050] (5) performing wet spinning under a stable magnetic field with a magnetic field strength of 0.5 T, a spinning temperature of 70° C., an aqueous solution of dimethyl sulfoxide (DMSO) as a coagulation bath, a coagulation bath concentration of 60 wt %, and weaving to obtain a fabric;
[0051] (6) The fabric was evaporated at 200°C, 0.6 MPa and nitrogen protection for 3 h to obtain a fabric precursor, and the fabric precursor was heated in a constant temperature water bath at 70°C with deionized water for 15 min, dried at 70°C, and then heated in a constant temperature water bath at 50°C with anhydrous ethanol for 15 min, ultrasonically treated at 25 kHz for 15 min, and dried at 70°C. The deionized water washing was repeated three times, and the thermal insulation fabric was obtained after drying at 70°C.
[0052] Comparative Example 1
[0053] The difference between Comparative Example 1 and Example 1 is that step (2) is different. Step (2) is changed to: tetrabutyl titanate and acrylic acid are mixed in a mass ratio of 0.5:1, the mass ratio of acrylic acid to silica aerogel is 1, and then 50wt% ethanol aqueous solution with a total mass of 2 times is added, and stirred at 600r / min for 4h to obtain a titanium dioxide reaction solution; the remaining steps are the same as in Example 1.
[0054] Comparative Example 2
[0055] The difference between Comparative Example 2 and Example 1 is that step (2) is different. Step (2) is changed to: PU500 polyurethane and tetrabutyl titanate are mixed in a mass ratio of 1:0.5, the mass ratio of polyurethane to silica aerogel is 1, and then 50wt% ethanol aqueous solution with a total mass of 2 times is added, and stirred at 600r / min for 4h to obtain a titanium dioxide reaction solution; the remaining steps are the same as in Example 1.
[0056] Comparative Example 3
[0057] The difference between Comparative Example 3 and Example 1 is that step (5) is different. Step (5) is changed to: wet spinning of the spinning solution, the spinning temperature is 60°C, an aqueous solution of dimethyl sulfoxide is used as a coagulation bath, the coagulation bath concentration is 50wt%, and weaving is performed to obtain a fabric; the remaining steps are the same as in Example 1.
[0058] Comparative Example 4
[0059] The difference between Comparative Example 4 and Example 1 is that step (6) is different. Step (6) is changed to: the fabric is heated in a constant temperature water bath with deionized water at 60°C for 10 minutes, then dried at 70°C, then heated in a constant temperature water bath with anhydrous ethanol at 40°C for 10 minutes, ultrasonically treated at 20kHz for 10 minutes, dried at 70°C, and then washed with deionized water twice, and dried at 70°C to obtain the thermal insulation fabric.
[0060] Effect example
[0061] Table 1 below shows the performance analysis results of the thermal insulation fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 4.
[0062] Table 1
[0063]
[0064]
[0065] From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 1, it can be found that polyurethane has excellent mechanical and chemical properties, can improve the flexibility, compressive strength and high temperature resistance of silica aerogel, and can also be used as a viscous agent to make the silica particles more firmly bonded, thereby improving the thermal insulation effect of the fabric. At the same time, polyurethane can also catalyze tetrabutyl titanate to prepare nano titanium dioxide, thereby improving the anti-ultraviolet performance of the fabric. From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 2, it can be found that acrylic acid can enhance the activity of amino groups on the surface of polyurethane, improve the ability of polyurethane to catalyze tetrabutyl titanate to prepare nano titanium dioxide, thereby improving the anti-ultraviolet performance of the thermal insulation fabric. External line performance; From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 3, it can be found that applying a magnetic field can adjust the morphology of nano-titanium dioxide and improve its ultraviolet protection effect; From the comparison of the experimental data of Examples 1, 2, and 3 with Comparative Example 4, it can be found that after the decomposition of acrylic acid, elongated nano-grooves and holes will be left in the fabric. The introduction of the elongated nano-groove structure can greatly increase the contact area between the fibers, thereby improving the interface interaction. This interface effect makes a great contribution to the friction effect, which doubles the tensile strength of the material, and the nano-grooves and holes can greatly increase the heat transfer path, thereby making the fabric have an ultra-low thermal conductivity.
[0066] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A thermal insulation fabric, characterized in that: The heat-insulating fabric is prepared by wet spinning modified silica aerogel and polyamide fiber and then oxidizing acrylic acid at high temperature.
2. A thermal insulation fabric according to claim 1, characterized in that: The modified silicon dioxide aerogel is prepared by adding acrylic acid, polyurethane and tetrabutyl titanate into the silicon dioxide aerogel, and then using the modified polyurethane to catalyze the tetrabutyl titanate to prepare nano titanium dioxide.
3. A method for preparing a thermal insulation fabric, characterized in that: The method comprises the following preparation steps: (1) mixing a dispersant, a wetting dispersant and deionized water in a mass ratio of 0.11-0.15:0.09-0.11:1, ultrasonicating at 30-40 kHz for 10-30 minutes, stirring at 700-800 r / min for 1-2 hours to obtain a mixed solution, adding 0.07-0.08 times the mass of the mixed solution of silica aerogel, stirring at 800-1000 r / min for 30-60 minutes to obtain a reaction solution; (2) adding 2 / 3 of the titanium dioxide reaction solution to the reaction solution, and dropping the remaining 1 / 3 of the titanium dioxide reaction solution under stirring at 500-600 r / min. After the dropping is completed, standing at room temperature for 4-5 hours, adding 0.2-0.3 times the mass of the reaction solution of pretreated polyamide pellets, stirring at 200-300 r / min for 3-6 hours, and standing at room temperature for 4-5 hours to obtain a spinning solution; (3) performing wet spinning and weaving under a stable magnetic field to obtain a fabric; (4) The fabric is evaporated for 3 hours at 180-200° C., 0.5-0.6 MPa and nitrogen protection to obtain a fabric precursor, and then washed to obtain a thermal insulation fabric.
4. The method for preparing a thermal insulation fabric according to claim 3, characterized in that: In the step (1), the dispersant is one of SN-5040, DN500 and HY-1010; the wetting dispersant is one of PE-100, LD-1055 and HR-8060.
5. The method for preparing a thermal insulation fabric according to claim 3, characterized in that: The preparation method of the titanium dioxide reaction liquid in the step (2) is: PU500 polyurethane, tetrabutyl titanate, and acrylic acid are mixed in a mass ratio of 1 to 2:0.5 to 1:1, the mass ratio of polyurethane to silica aerogel is 1, and then 2 to 3 times the total mass of 50wt% ethanol aqueous solution is added, and stirred at 600 to 800 r / min for 4 to 6 hours to obtain the titanium dioxide reaction liquid.
6. The method for preparing a thermal insulation fabric according to claim 4, characterized in that: The preparation method of the pretreated polyamide pellets in step (2) is as follows: the polyamide pellets are mixed with the TEGIN Pellets aqueous solution at a ratio of 1:10, soaked for 4 to 6 hours, and then placed in a vacuum drying oven at 100 to 120° C. and 50 to 60 kPa for 2 to 3 hours to obtain the obtained product.
7. The method for preparing a thermal insulation fabric according to claim 6, characterized in that: The concentration of TEGIN Pellets in the TEGIN Pellets aqueous solution is 30-40 g / L.
8. The method for preparing a thermal insulation fabric according to claim 3, characterized in that: The process parameters of wet spinning in step (4) are as follows: the spinning temperature is 60-70° C., the aqueous solution of dimethyl sulfoxide is used as the coagulation bath, and the coagulation bath concentration is 50wt%-60wt%.
9. The method for preparing a thermal insulation fabric according to claim 3, characterized in that: The magnetic field strength of the stable magnetic field in step (4) is 0.35-0.5T.
10. The method for preparing a thermal insulation fabric according to claim 3, characterized in that: Washing in step (4): the fabric precursor is heated in a constant temperature water bath at 60-70°C with deionized water for 10-15 minutes, then dried at 70°C, then heated in a constant temperature water bath at 40-50°C with anhydrous ethanol for 10-15 minutes, ultrasonically treated at 20-25kHz for 10-15 minutes, then dried at 70°C, and then the deionized water washing is repeated 2-3 times.
Citation Information
Cited By
Heat insulation fabric and preparation method thereof
CN120738791A
Heat-insulating and ultraviolet-proof polyester film for automobile and preparation method of heat-insulating and ultraviolet-proof polyester film
CN121004820A
Fabric with moisture permeability, air permeability and ultraviolet resistance and preparation method thereof
CN122189920A
A fabric with moisture-conducting, air-permeating and ultraviolet-resistant properties
CN122189920B